2008
DOI: 10.1021/bi702223c
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Insertion Pathway of Annexin B12: Thermodynamic and Kinetic Characterization by Fluorescence Correlation Spectroscopy and Fluorescence Quenching

Abstract: Experimental determination of the free energy stabilizing the structure of membrane proteins in their native lipid environment is undermined by the lack of appropriate methods and suitable model systems. Annexin B12 (ANX) is a soluble protein which reversibly inserts into lipid membranes under mildly acidic conditions, which makes it a good experimental model for thermodynamic studies of folding and stability of membrane proteins. Here we apply fluorescence correlation spectroscopy for quantitative analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
83
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
3

Relationship

4
2

Authors

Journals

citations
Cited by 36 publications
(86 citation statements)
references
References 56 publications
3
83
0
Order By: Relevance
“…LUV (large unilamellar vesicles) containing the quencher LysoUB (to allow monitoring the binding process via quenching of the bimane probe (Ladokhin et al, 2002; Posokhov & Ladokhin, 2006; Posokhov et al, 2008b)) were composed of a mixture of POPC:POPG with a 9:1 molar ratio, which has been demonstrated to stabilize the interfacial intermediate state and prevent further insertion into the bilayer (Kyrychenko et al, 2009). In order to further exclude the possibility of transmembrane insertion and limit the observation to the interfacial intermediate, the measurements were performed at the mildly acidic pH of 6.0.…”
Section: Resultsmentioning
confidence: 99%
“…LUV (large unilamellar vesicles) containing the quencher LysoUB (to allow monitoring the binding process via quenching of the bimane probe (Ladokhin et al, 2002; Posokhov & Ladokhin, 2006; Posokhov et al, 2008b)) were composed of a mixture of POPC:POPG with a 9:1 molar ratio, which has been demonstrated to stabilize the interfacial intermediate state and prevent further insertion into the bilayer (Kyrychenko et al, 2009). In order to further exclude the possibility of transmembrane insertion and limit the observation to the interfacial intermediate, the measurements were performed at the mildly acidic pH of 6.0.…”
Section: Resultsmentioning
confidence: 99%
“…To circumvent this limitation one has to switch from peptides to more complex protein systems to study the energetics of membrane insertion such as annexin B12 and diphtheria toxin T-domain. Both of these proteins undergo a reversible pH-dependent membrane insertion (Ladokhin and Haigler, 2005; Ladokhin et al , 2004) which makes them attractive models for thermodynamic and kinetic studies using fluorescence correlation spectroscopy (FCS) and other spectroscopic approaches (Ladokhin et al , 2002; Posokhov et al , 2008a,b). …”
Section: Challenges Of Thermodynamic Analysis Of Membrane Protein mentioning
confidence: 99%
“…Due to recent technical developments, FCS is gaining popularity in biological studies (Haustein and Schwille, 2003; Hess et al , 2002; Schwille et al , 1999). Several groups have utilized it to study interfacial binding and transmembrane insertion of peptides and proteins (Posokhov et al , 2008a,b; Rhoades et al , 2006; Rusu et al , 2004). Rusu et al (2004) compared FCS results to those available from other measurements and found them to be in excellent agreement, opening the doors for quantitative application of FCS to membrane protein binding.…”
Section: Fcs and Protein–membrane Interactionsmentioning
confidence: 99%
See 2 more Smart Citations